A Freirean analysis of the Escola sem Partido dystopian schooling model: indignation, hope and untested feasibility during pandemic times. (3rd July 2022) - Knijnik, Jorge
ABSTRACT: This paper examines contemporary challenges for education and democracy in Brazil. In the past decade, conservative forces headed by the Escola sem Partido (ESP) movement have led a scaremongering campaign against teachers and public education, with Paulo Freire's critical educational philosophies as their main enemy. This study investigates the ESP's attempts to implement its 'neutral' education model based in traditional values across the country. Key Freirean concepts combined with Horsford '3Rs' agenda to regain democracy in schools are used to analyse the media narratives presented by the ESP and civil movements that have resisted its efforts to undermine democracy within Brazilian schools. The findings suggest that the ESP's bullying tactics have been effective in undermining teachers' autonomy in many Brazilian schools. Further tensions have been provoked by the pandemic within the public educational system. Conversely, Freirean-inspired school communities have found new ways to counteract this harassment and strengthen democratic pedagogies.